Efektivitas Penggunaan Knapsack Sprayer Elektrik dalam Pengendalian Gulma Tanaman Kelapa Sawit (Elaeis guineensis Jacq) - Firman RL. Silalahi; Ameilia Zuliyanti; Doli Syahputra Siregar (Jurnal Sosial Ekonomi Pertanian, 2023)
Absract This study aims to determine the effectiveness of the use of an electric knapsack sprayer in controlling weeds in oil palm plants. This study was carried out in Sirapit District, Langkat Regency from April to June 2022. The data collection methods used were questionnaires/questionnaires and interviews. The analytical method used is a Likert scale to determine the level of effectiveness and multiple linear regression to determine the factors that affect the effectiveness of using an electric knapsack sprayer in controlling weeds on palm oil plants in Sirapit District, Langkat Regency. For the F test, Fcount is 8.463 > Ftable 2.18, which means that simultaneously the variables of age, education, the role of extension agents, experience, land conditions, expertise, and operational costs have a significant effect on the effectiveness of using electric knapsack sprayers in weed control. on oil palm plantations. For the partial t-Test, the factors that significantly affect the effectiveness of using electric knapsack sprayers in controlling weeds in oil palm consist of the role of extension workers (t=3.424), land conditions (t=4.734), expertise (t=2.550), and operational costs (t=3.556), but it is not significantly for three factors, such as age (t=-1.302), education (t=0.854), and experience (t=-0.574). The results of this study showed that the effectiveness of using an electric knapsack sprayer in controlling weeds in oil palm was high (80.27%). Factors that influence the effectiveness of using electric knapsack sprayers in controlling weeds in oil palm plantations are the role of extension workers, land conditions, expertise, and operational costs. Keywords:  Effectiveness, electric knapsack sprayer, palm oil, herbicide, weed